The Effects of Consumption Habits and Borrowing on Working Life in the Context of Employee Poverty - Furkan Düzenli (Sosyal Siyaset Konferansları Dergisi)
As a global problem, labour poverty is one issue worth discussing in the literature. Especially when the predicaments of working life are considered, the problem gains a different dimension because wages, which are the only means at the disposal of the individual, cannot offer the life expected from social life and that consumption cannot keep up with it while production is progressing at full speed. There is no doubt that the frenzy of consumption, expressed as the sine qua non-of today’s world, will lead individuals to a path of debt. Therefore, the individual inevitably continues his/her life by incurring debt in the frenzy of consumption, and at the point where he/she experiences deprivation, he/she only realises that he/she has entered an irreversible path. After this point, the individual finds himself/herself in a passive rather than active state with altered expectations in working life. Thus, the employees who change the system and experience the biggest problems within the changing system remain in a position to serve the cogs of capitalism and cannot be themselves in the social field, and their view of work changes. The phenomenon of "working poverty", which this study is based on, can be seen as the starting point of some social and economic problems that labour life has frequently referred to in recent years. Therefore, the solution to this problem will make positive contributions to the transformation of working life and contribute to the individual’s living a more prosperous life under more human conditions. In this sense, the study discusses working poverty, consumption habits, and indebtedness and examines the effects of these phenomena on working life. The study was carried out with a literature review, which is one of the qualitative research methods, document analysis was used to analyse the data related to working life, and content analysis was used to analyse the data. Therefore, the impact of consumption habits and forms of borrowing on workers’ poverty is expressed.